The concept of “national security” in Kazakhstan - М.О., Мусaбеков (Journal of Oriental Studies, 2019)
The concept of “national security” is not something unchanged and may change depending on the historical, political, economic conditions and the emergence of unexpected threats and challenges for the state and the people. Ensuring national security is the fundamental responsibility of any government. Without feeling secure, people cannot trust their government, local government structures, even their neighbors, nor can they focus on their daily needs and activities, their shortterm and longterm goals, because they are concerned about their ability to provide wellbeing and normal living conditions. to their families or to plan adequately for the future. Without reliance on the foundation of personal and collective security, people work in an extremely unstable environment that does not contribute to their traditional functioning as members of society and leads to a serious distrust that they have in all institutions and individuals in power. Many societies around the world face this global and daily challenge in trying to provide the practically necessary elements of a security system in the lives of their citizens (1). The last few decades were marked by the gradual transition of humanity from industrial society to the age of information technology. The development of communication technologies and the wide distribution of electronic devices associated with this process create new threats that will be considered in this paper. Key words: cyber security, cyber defense, cyberspace, cyberterrorism, national security.